Pemanfaatan Media Buku Cerita Guna Meningkatkan Kemampuan Membaca Siswa SD Negeri 064985 - Taufiq Ramadhan; Tuti Atika (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
Good reading ability is an important skill in the learning process that affects overall academic achievement. Story books were chosen as the main media because they combine text with interesting pictures, which can stimulate students' interest and imagination. The use of storybook media can effectively improve students' reading skills. This media provides a fun learning experience and motivates students to be involved in the reading process. Therefore, the purpose of this writing is to improve the reading ability of SD Negeri 064985 students by using story books as media. The location of the author's field work practice is on Jl. Captain Muslim No. 240b, Helvetia, Kec. Medan Helvetia, Medan City, North Sumatra. As well as in this practice using the groupwork method by Zastrow. The stages in the groupwork method include (1) Engagement, Intake, Contract, (2) Assessment, (3) Planning, (4) Intervention, (5) Monitoring, (6) Evaluation, and (7) Termination. The results obtained from these practical activities showed an increase in students' reading skills, and there was progress in student academic achievement.